Creep-Overpressure Coupling in The Onshore of Northeast Java Basin: Structural and Field-Based Geological Constraints - Eri S. Sitinjak; Benyamin Sapiie; Agus M. Ramdhan (Geological Agency, 2026)
The onshore Northeast Java Basin is one of the most important oil and gas basins in Indonesia. The active Kendeng Fault plays a significant role in hydrocarbon generation and earthquake activity in the region. Studying the Kendeng Fault activity and its relationship with overpressure and earthquake potential could improve oil and gas exploration activities as well as natural disaster mitigation efforts in the onshore areas of the Northeast Java Basin. Therefore, this research focuses on surface geological mapping and laboratory analysis of field samples. Fault creep in the onshore of the Northeast Java Basin has not been studied continuously. Active mud volcanoes, which result from subsurface overpressure, may influence the creep rate and activity of Kendeng Fault segments. The Kendeng Fault meets the criteria of a creeping fault due to its geology, subsurface overpressure conditions, and geometry. Manifestations of creep near fault planes are clearly visible through geological phenomena such as landslides or physical changes in buildings. The Central Java morphology (Grobogan area) is rougher than The East Java morphology (Surabaya area), which suggests a possible difference in creep rate. The focal mechanism of recent earthquakes in the Kendeng Fault Zone indicates strike-slip or thrust faulting. The Central Java Fault segment exhibits a faster creep rate than the East Java Fault segment. This is evident through swarms of earthquakes at Gunung Pandan and Rawa Bening. Elemental analysis of the fluid and mud, combined with gas analysis of all the mud volcanoes in the studied area, shows a positive correlation between possible halide minerals (Na, Mg, Ca, K, and Cl) and gas content (N₂ and O₂/Ar). There is also a slight relationship between these gas and fluid elements (R²). These parameters increase from the mud volcanoes in East Java to those in Central Java. CO₂ shows a negative correlation (r) and a slightly stronger relationship (R²) with CH₄. The mud volcanoes in Central Java are dominated by CO2, which may originate from volcanic activity in a deeper reservoir as a result of tectonic activity in the region. In contrast, the mud volcanoes in East Java are dominated by CH₄, which may originate from a highly overpressured hydrocarbon reservoir in a shallower area due to a high sedimentation rate. The very high sedimentation rate influences the slow-creeping fault segment in East Java (the Surabaya region) due to overpressure. Conversely, the faster creeping fault segment in Central Java (the Grobogan and Kesongo areas) may be influenced by volcanism due to tectonic activity in the region. These findings require further study, particularly the relationship of overpressure in each Kendeng Fault segment. The results will be useful for hydrocarbon exploration activities in the region as well as for natural disaster mitigation in general.